Habitual caffeine use in psychiatric patients: relationship with sleep quality and symptom severity - Mermi, Osman; Kilic, Faruk; Gurkan Gurok, Mehmet; Yilmaz, Seda; Baykara, Sema; Canan, Fatih; Kuloglu, Murat (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2016)
Objective: The purpose of this study was to investigate the patterns of caffeine use and the one-month prevalence of caffeine intoxication among psychiatric patients in comparison with healthy controls. Methods: Four hundred and one patients with various psychiatric disorders and 150 healthy controls were screened for current (one month) caffeine intoxication according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition. All participants were asked to complete Pittsburgh Sleep Quality Index (PSQI). The patients were also assessed with the Clinical Global Impression Scale (CGI) to determine symptom severity. Results: The amount of daily caffeine consumption was statistically significantly higher in healthy control subjects than in patients. However, the prevalence of caffeine intoxication was greater among patients with a psychiatric disorder (8%) when compared with healthy controls (2.7%). In the patients, the amount of caffeine consumption correlated positively with age, CGI, and PSQI scores, indicating that patients with older age, poorer sleep quality, and more severe pathology consumed higher amounts of caffeine. Conclusions: Caffeine intoxication was more prevalent in psychiatric patients than in healthy subjects. The amount of caffeine intake was shown to be associated positively with the severity of pathology and inversely with sleep quality. Further studies are needed to investigate the effect of regulating caffeine consumption on severity of pathology and sleep quality among psychiatric patients.
Psikiyatri hastalarında kafein kullanma alışkanlığı: Uyku kalitesi ve belirti şiddeti ile ilişkisi
Keywords: habitual caffein use; psychiatric patients; prevalence; sleep quality